Mapping current research and identifying hotspots of ferroptosis in cardiovascular diseases - Teng, Teng; Kong, Chun-Yan; Huang, Rong; Ma, Zhen-Guo; Hu, Can; Zhang, Xin; Hu, Min; Tang, Qi-Zhu (Frontiers in Cardiovascular Medicine, 2022)
Objective: Ferroptosis is a unique cell death depended on iron metabolism disorder which is different from previous apoptosis-regulated cell death. Early studies have proposed that ferroptosis is closely associated with multiple cardiovascular diseases (CVDs). However, the relationship of ferroptosis CVDs has not been summarized by using bibliometric analysis. We intended to illustrate the development of ferroptosis in CVDs over the past years and provide relevant valuable information. Methods: The authoritative database of Web of Science Core Collection was collected for retrieving ferroptosis studies in CVDs. In this work, statistical and visualization analysis were conducted using VOSviewer and Citespace. Results: A total of 263 studies were included in the final study. From the perspective of the overall literature, the study maintains an increased trend year by year and most manuscripts belonged to original article. China was the most productive country with the utmost scientific research output, as well as the institutions and authors, followed by Germany and the United States of America (USA). Jun Peng from China contribute to the most publications. Collaborative efforts between institutes and authors were limited and there was little widespread cooperation. In addition, burst keywords analysis discovered that ischemia-reperfusion(I/R) injury, heart failure (HF), and atherosclerosis were the top three research directions of ferroptosis in CVDs. The burst investigation and timeline views also indicated that endothelial injury and gut microbiota may also be new research topics in the future. Conclusions: This study provided comprehensive and specific information about the most influential articles on ferroptosis in CVDs. The relationship between ferroptosis and CDVs had attracted the scholar’s concern especially in China. Cooperation and communication between countries and institutions should be emphasized and future direction can be concentrated on endothelial disorder and gut microbiota.